Is Probiotics Supplementation an Appropriate Strategy to Modulate Inflammation in Physically Active Healthy Adults or Athletes? A Systematic Review - Diego Fernández-Lázaro; Nerea Sánchez-Serrano; Roshina Rabail; Rana Muhammad Aadil; Juan Mielgo-Ayuso; Krizia Radesca Fabiano; Evelina Garrosa (Applied Sciences, 2023)
Supplementation with probiotics in sports is on the rise with the aim of improving health and athletic performance. Since intense exercise-induced muscle damage leads to an inflammatory process by increasing circulating inflammatory cytokines, probiotic supplementation may modulate and correct the inflammation. We systematically reviewed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines in the Scopus, Web of Science, and Medline databases for the 10 years until January 2023. This review aimed to evaluate probiotic supplementation as a strategy for modulating inflammation in healthy physically active adults or athletes. Studies were indexed to assess the effect of probiotic supplementation on cytokine behavior in the inflammatory response in physically active individuals. Of the 136 studies identified in the search, 13 met the inclusion criteria, and their quality was assessed using the McMaster Critical Review Form. The results of these trials indicated a significant improvement in inflammatory cytokines in probiotic-supplemented participants, with a significant increase in anti-inflammatory cytokines (IL-10) and a significant decrease in proinflammatory cytokines (IL-6, TNF-α, and IL-8). This would create uncertainty about probiotics’ effect on interleukins’ behavior after exercise, and further clinical trials are needed to establish a solid basis.